ANALISIS YURIDIS TRADISI PERKAWINAN DAN PEMBAGIAN WARISAN DALAM ADAT KARO MERGA SILIMA DI DESA MERDEKA - Gio Fani Sembiring Pandia; Rayani Saragih; Maria Ferba Editya (Journal Recht (JR), 2025)
This study analyzes the marriage tradition and inheritance distribution mechanism in the Karo Merga Silima custom in Merdeka Village. The approach used is empirical juridical with qualitative descriptive methods. The results of the study indicate that the Karo customary marriage tradition is carried out through several sacred stages such as Mbaba Belo Selambar, Nganting Manuk, and Kerja Adat. Meanwhile, the distribution of inheritance follows a patrilineal system, where sons obtain primary rights to inheritance, while daughters only receive a share based on affection. This study emphasizes the importance of customary deliberation (runggu) in maintaining the harmony of inheritance distribution.